Comparative analysis of antihypertensive effects of chlorthalidone and indapamide-retard in combination with azilsartan medoxomil in patients with arterial hypertension - Zh. D. Kobalava; V. V. Kulakov; L. A. Goreva; S. V. Villevalde (Российский кардиологический журнал)
Achievement of target blood pressure (BP) is one of the key strategies of primary prevention of cardiovascular complications in patients with arterial hypertension (AH). Aim. To assess and compare antihypertensive effects of azilsartan medoxomil (AZM) with chlorthalidone or indapamide-retard combination in patients with AH in real clinical setting.Material and methods. The open randomized comparative study included 50 patients with uncontrolled AH who were randomized to the starting therapy with combination of AZM with chlorthalidone (Edarbi Clo 40/12,5 mg) (group 1) or indapamide-retard 1,5 mg (group 2) for 4 weeks. After 4 weeks, up-titration of one of the drugs was done in the patients who didn’t achieve target BP level (<140/<90 mm Hg): chlorthalidone from 12,5 mg to 25 mg in G1 and AZM from 40 to 80 mg in group 2. Duration of the study was 12 weeks. Treatment efficacy was assessed by the target office BP achievement and changes in 24-h peripheral and central BP. Results were considered statistically significant at p<0,05.Results. At the end of the 12-week period target BP was achieved in 88% of group 1 and 72% of group 2 patients. According to 24-h blood pressure monitoring (ABPM) mean peripheral BP decline was 19,3/11,1 vs 17,1/9,1 mm Hg for 24h, 20,1/11,4 vs 19,1/9,9 mm Hg for daytime, 19,5/9,1 vs 17,6/8,9 mmHg for nighttime (p<0,05 for trend). Target 24-h BP levels <130/<80 mm Hg were achieved in 40 vs 32% of patients respectively (р<0,05). Increase of the portion of dippers was observed from 60 to 64% and from 58 to 62% respectively (p<0,05).Conclusion. In patients with uncontrolled AH combination of AZM with chlorthalidone compared has led to more pronounced antihypertensive effect compared to combination of AZM with indapamide-retard.